2023
DOI: 10.31083/j.rcm2411310
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure: Is There an Ideal Biomarker?

Giuseppe Clemente,
John Sebastian Soldano,
Antonino Tuttolomondo

Abstract: An always-rising prevalence of heart failure (HF), formerly classified as an emerging epidemic in 1997 and still representing a serious problem of public health, imposes on us to examine more in-depth the pathophysiological mechanisms it is based on. Over the last few years, several biomarkers have been chosen and used in the management of patients affected by HF. The research about biomarkers has broadened our knowledge by identifying some underlying pathophysiological mechanisms occurring in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…The study revealed that higher sST2 concentrations are strongly correlated with adverse outcomes. 31,32 A systematic review and meta-analysis by Ip et al demonstrated that elevated levels of sST2 are a predictor of severe chronic HF and tend to be associated with a higher risk of mortality in chronic HF and stable CAD. 29 A prospective study by Rezar et al also suggests measuring serum sST2 levels 24 h after admission for prognostication after cardiopulmonary resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that higher sST2 concentrations are strongly correlated with adverse outcomes. 31,32 A systematic review and meta-analysis by Ip et al demonstrated that elevated levels of sST2 are a predictor of severe chronic HF and tend to be associated with a higher risk of mortality in chronic HF and stable CAD. 29 A prospective study by Rezar et al also suggests measuring serum sST2 levels 24 h after admission for prognostication after cardiopulmonary resuscitation.…”
Section: Introductionmentioning
confidence: 99%